Las primeras bibliotecas de Roma (Romoteca) - Alonso Troncoso, VÍCTOR (Revista General de Información y Documentación, 2003)
The aim of this article is to give an up-to-date outline of the development of the first libraries in ancient Rome, from the end of the Republic to the first century of the Principate (I B.C.-I A.D.) Both private and public libraries are studied and attention is given not only to architectural and librarian aspects but also to the political and sociological conditions of reading in antiquity.